Análisis del enfoque informativo que dan los medios televisivos a la violencia intrafamiliar y su incidencia en las calles Gómez Rendón hasta Venezuela y de la 24 hasta la 29 suburbio - Heredia Villalta, Mónica Vanessa (2016)
The present research is to analyze the informative approach that give the television media to domestic violence and its impact on the streets Gómez Rendón to Venezuela and 24 to 29 (Suburb). The purpose is to determine reasons that lead people living in low-income consume crime reports related news, as well as why the media are in such notes potential niche markets…..